Investigation of underwater acoustic multi-path Doppler and delay spreading in a shallow marine environment - Caley, Michael; Duncan, Alec (Australian Acoustical Society, 2013)
Doppler frequency spreading and arrival delay spreading of underwater acoustic communication signals under the influence of surface waves and transmitter-receiver motion were investigated in a channel probing experiment conducted primarily with binary pseudo-noise (PN) sequences ranging from 21ms to 1.4s duration. Testing was conducted in a 13.5m deep environment at transmission distances ranging from 44m to 1007m. The channel Doppler response was investigated both by time-domain Doppler search of the transmit-receive correlation for successive repeats of a 1.4s probe sequence, and by Fourier analysis of the channel impulse response history from a repeated 21ms probe sequence (i.e. Spreading Function). The bounds of Doppler shift imparted by relative transmitter/receiver motion and surface wave motion to idealised soundray transmission paths has been compared with experimental Doppler indicated by the Spreading Function. The coherence of the experimental channel response was also examined for different propagation ranges and at different delayed arrivals of the experimental signals.